Outage probability versus the transmit power budget, with N = 5, = 5, m = 1, = 5 [dBm] and = = 1.5 [BPCU]. - Minh Tran (7698803) (2025)
Outage probability versus the transmit power budget, with N = 5, = 5, m = 1, = 5 [dBm] and = = 1.5 [BPCU].